Trade finance gaps, growth, and jobs survey. - DiCaprio, Alisa (ADB Briefs., 2017)
This brief discusses the 2017 ADB Trade Finance Gaps, Growth, and Jobs Survey which quantifies global market gaps for trade finance and the impact on growth and jobs.